Changes in media consumption and its impact in modern advertising: a case study of advertising strategies in Ecuador - Melissa Espinoza; Norman Cevallos; Aleksandar Tusev (Innova Research Journal)
Digital Marketing has become an essential tool for modern advertising agencies. Companies that do not consider this fact are in danger of becoming obsolete. Social media has taken center stage with millennials, offering advertisers viral growth opportunities. As such, media consumption habits are changing ever faster worldwide. In Ecuador, digital marketing is beginning to be taken seriously, yet it is still not occupying the optimal attention in order to capture the millennial market niche that surely exists. This study analyses the transition from traditional to digital marketing, with a case study analysis of Ecuador, a Latin American nation in the process of adopting these modern advertising tools. Furthermore, the research here describes the new concepts implemented in the industry and seeks to identify if digital marketing will replace traditional media any time soon. In order to analyze these topics, interviews with industry experts were conducted. As a result, it was found that digital marketing has not been used at a rate of maximization, instead the focus has continued to be on more traditional marketing strategies. This strategy has proven to still be the safest and most effective one in this market; however, advertisers need to start planning for dynamic shifts that much of the Western world has already moved on to, or risk the possibility of being left behind.